Gaining an understanding of Umnyama from the Zionist churches: a case study of Zimbabwean migrants in Johannesburg, South Africa - Zulu, Melekias (My University, 2012)
When migrants move, they move with their religious beliefs and practices. What happens to those religious beliefs and practices in the country of migration? Is there change or continuity in religious affiliation? While much of the literature on Zimbabweans is largely focused on their reasons for migration, the policies, laws and difficulties they encounter in South Africa; this study examines how Zimbabwean migrants use religion in the host country. This study investigates if and how migration affects Zimbabwean migrants’ religious beliefs and practices. This study explores how Zionist churches respond to the existential needs of migrants and their worldviews; specifically looking at the responses offered to metaphysical challenges like umnyama (misfortune) of Zimbabwean migrants in Johannesburg.
M.A., Faculty of Humanities, University of the Witwatersrand, 2011